Sculpting the Science: Teaching Anatomy of the Facial Muscles to Medical Students - Toni Chiappini; Janine C Correia; Adam M Taylor; Jan van der Merwe; Quenton Wessels (International Journal of Medical Students)
Background:Clay-modeling in anatomy education is an engaging activity that complements cadaveric dissections. The post-COVID-19 cadaver shortage further necessitates alternative practical modalities.